Uses and applications of Software & Systems Process Engineering Meta‐Model process models. A systematic mapping study. Issue 9 (10th April 2013) - Ruiz‐Rube, Iván; Dodero, Juan Manuel; Palomo‐Duarte, Manuel; Ruiz, Mercedes; Gawn, David
SUMMARY: Software process engineering is a discipline, which aims to study and improve software development and maintenance processes. The explicit definition of software processes is essential. To this end, the Object Management Group consortium proposed the Software & Systems Process Engineering Meta‐Model (SPEM) that exploits the benefits of the Model Driven Architecture paradigm applied to software process models, instead of software specification models. The aim of this study is to discover evidence clusters and evidence deserts in the use and application of SPEM from a business process management point of view. To reach the proposed objective, we have undertaken a systematic mapping study of the existing scientific literature. The reviewed literature deals mainly with process modeling and, to a lesser extent, with process adaptability, verification, and validation, enactment and evaluation. Wide agreement exists in using the SPEM meta‐model to develop different types of methods and processes. Further research efforts are needed in areas related to enactment and evaluation of software processes. There is a need to evolve to a new version of the meta‐model that incorporates the improvements proposed by different authors. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : This paper presents a systematic mapping study on the uses and applications of software process models defined with Software & Systems Process Engineering Meta‐Model. The study analyzes the possibilities that Software & Systems Process Engineering Meta‐Model models offer in the Business Process Management life cycle. The reviewed literature mainly deals with process modeling, by developing either processes models or frameworks. The obtained results lack sufficient works related to the assessment of industrial implementations.